Analysis of Brand Awareness and Brand Image Strategies on Lake Toba Tourists' Interest through the F1H20 Power Boat Digital Marketing Strategy in Balige, North Tapanuli - Pranata, Sungguh Ponten; Sinaga, Anggiat (Journal of Business Management and Economic Development, 2023)
The main objective of this study is to analyze the effect of brand awareness and brand image on the interest of Lake Toba tourists through digital marketing strategies. The approach used in this research is associative and quantitative, using path analysis. The population and sample of this study were micro, small, and medium enterprises around the location of the Lake Toba Powerboat F1H20 event in Sibola Hotang Village, Balige District, Samosir Regency, North Sumatra Province, totaling 93 people. The sampling technique used is quota sampling. The sample size in this study consisted of 93 respondents. The results showed that the effect of brand awareness on visitor interest had an original sample size of 0.550, P-Value 0.000 < P-Table 0.05, and T-value 4.374 > T-Table 1.196. The effect of brand image on visitor interest has an original sample size of 0.507, a P-value of 0.036, a P-table of 0.05, and a T-value of 3.666. T-Table 1.196. The effect of brand awareness through digital marketing on visitor interest has an original sample of 0.235 with a P-Value of 0.040 < P-Table 0.05 and a T-value of 2.051 > T-Table 1.196. The influence of brand image through digital marketing on visitor interest has an original sample of 0.435 with a P-Value of 0.040 (P-Table 0.05) and a T-Value of 3.051. T-Table 1.196. Finally, the effect of digital marketing on visitor interest has an original sample size of 0.435, a P-Value of 0.040, a P-table of 0.05, and a T-value of 3.051. T-Table 1.196.